(untitled) (Vietnam Journal of Community Medicine, 2023)
Aims: To determine the proportion of pediatricians with anxiety, stress, depression and stress during the COVID-19 pandemic at the National Children’s Hospital in 2020 -2022. Methods: A cross-sectional descriptive study on 239 pediatricians who were present at work at the time of the study and used the DASS scale to assess the mental health of pediatricians. Results: Mean age was 46.1, and under 35 years old accounted for 42,9%. 54,8% are female and 85.4% are married and living with a partner. Participation in management accounts for 29,7%. According to the DASS21 scale, the depression rate of doctors is 14.6%, of which 0.8% is severe and 3.8% is very severe. The rate of anxiety among pediatricians was 17.2%, of which 2.1% were severe and 5% were very severe. The stress rate of health workers was 14.6%, in which 2.9% were severe and 2.1% were very severe. Conclusion: The COVID-19 pandemic has significantly impacted the mental health of pediatricians at the Vietnam National Children’s Hospital.